2000
DOI: 10.1053/jhep.2000.18714
|View full text |Cite
|
Sign up to set email alerts
|

Fine Specificity of T Cells Reactive to Human PDC-E2 163-176 Peptide, the Immunodominant Autoantigen in Primary Biliary Cirrhosis: Implications for Molecular Mimicry and Cross-Recognition Among Mitochondrial Autoantigens

Abstract: The anti-mitochondrial antibody response in primary biliary cirrhosis (PBC) is primarily directed at E2 components of PDC, OGDC, and BCOADC, and E3BP. Previous work has shown that the immunodominant autoreactive T-cell epitope is the PDC-E2 163-176 peptide, restricted by HLA DR53. To address molecular mimicry and cross-recognition among mitochondrial autoantigens, we analyzed reactivity, including agonism and antagonism assays, to a series of single amino acid-substituted peptides using cloned T-cell lines in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…The epitope does not appear to include the conserved lipoyl-binding lysine (K 173 ) although the 2 B-cell epitope regions flank the PDC-E2 163 to 176 peptide that constitutes the immunodominant autoreactive T-cell epitope. 45,46 The alignment of AIC-selected phagotopes to the PBC-specific branches of the peptide guide tree gives clear evidence that PBC and AIC are companion diseases, serologically at least, even though varying contributions to a multiplex pathogenesis may provide clinical individuality. Finally, our study illustrates the applicability of phage display coupled with multiple sequence alignments to the analysis of multifactorial immune-mediated diseases, with the promise of uncovering environmental agent(s) as the elusive trigger for the self-perpetuating pathology of PBC.…”
Section: Figmentioning
confidence: 99%
“…The epitope does not appear to include the conserved lipoyl-binding lysine (K 173 ) although the 2 B-cell epitope regions flank the PDC-E2 163 to 176 peptide that constitutes the immunodominant autoreactive T-cell epitope. 45,46 The alignment of AIC-selected phagotopes to the PBC-specific branches of the peptide guide tree gives clear evidence that PBC and AIC are companion diseases, serologically at least, even though varying contributions to a multiplex pathogenesis may provide clinical individuality. Finally, our study illustrates the applicability of phage display coupled with multiple sequence alignments to the analysis of multifactorial immune-mediated diseases, with the promise of uncovering environmental agent(s) as the elusive trigger for the self-perpetuating pathology of PBC.…”
Section: Figmentioning
confidence: 99%
“…Because the aetiology of PBC remains unclear, the goal in treating early-stage PBC is to slow the progression of disease and alleviate symptoms. Accumulated evidence by our group has demonstrated that autoreactive T cells that proliferate in response to mitochondrial autoantigens play a critical role in the destruction of the BECs [3][4][5][6][7]. Additionally, CD8 + T cells have been shown to predominate in the cellular infiltrates of portal tracts [3].…”
Section: Introductionmentioning
confidence: 99%
“…E. coli has been strongly associated with PBC (Bogdanos et al, 2010;Burroughs et al, 1984), largely due to the high occurrence of recurrent urinary tract infections in women with PBC (Corpechot et al, 2010;Gershwin et al, 2005). Experimental data support the presence of cross-reactive immune responses between human and E. coli PDC-E2 at the CD4 and CD8 T-cell level (Shigematsu et al, 2000;Van de Water et al, 2001). Several studies have demonstrated cross reactivity between the human PDC-E2 autoepitope (GDLLAEIETDKATI), and that of E. coli (EQSLITVEGDKASM) at the CD4 T cell level (Shimoda et al, 1995).…”
Section: Infectious Agents and Molecular Mimicrymentioning
confidence: 93%